Improvisação ao contrabaixo acústico com uso de arco na música popular brasileira instrumental (MPBI): estratégias de estudo e performance - ASSIS, Paulo Dantas de Paiva (2010)
This paper discusses the use of bowing technique in improvisation with the bass in the Brazilian Instrumental Popular Music (MPBI). The main objective is to develop study strategies through a brief literature review on the bowing technique, its application in North American jazz and the characteristics of improvisation in MPBI. Thus, the paper discusses the results and presents them in the form of suggestion implementation. The paper is organized into three parts: 1) Review of literature on the use of the bow on strings instruments, 2) MPBI improvisation and 3) strategies for improvisation study on double bass with the use of bowing technique in MPBI. It can be concluded that the processes involved in improvisation on the double bass with bowing technique in MPBI have some particularities that should be objects of attention and study. Moreover, there are similarities in the use of the bowing technique in Classical Music, particularly the technique preparation. It also follows that the greater the knowledge of the peculiarities of bowing technique in improvisation, preparing technical and stylistic knowledge of the bassist, the performance will be better.